Heat loss modelling and copper chelating from natural gas pipeline corossion - Hunt, D; Akindeju, Michael; Obanijesu, Emmanuel; Pareek, Vishnu; Tade, Moses (Elsevier, 2011)
Natural Gas at clients (downstream) terminals often burns with discolorations, with reduction in heat value and potential health hazard implications. One of the sources for the observed discolorations is a result of chelates (metallic compounds) fanned from process fluids due to equipment corrosion and erosion during the Natural Gas processing and transportation either through the pipeline or as LNG. This is of particular interest in Alkanolamine-based gas sweetening processes transported over aging/aged pipelines. With possible sources of ligands having available bonding sites, and the solubilised metallic central atoms in the processing and transport equipments, attainable formation and stability conditions all strongly suggest the imminence of chelation in Natural Gas/LPG processing and transportation. This work applied the Channiwala and Parikh correlations to model the chelate formation using Copper (Cu) as a base case, but also presents summary results for Iron (Fe) and Nickel (Ni) in Ethanolamine (MEA), Diethanolamine (DEA) and Ethylenediethanolamine (EDTA) based gas processing systems. All the Chelates considered were found to be them10dynamically within formation and stability bounds, resulting in a 0.5MJlkg (0.42MJ/m3 ) heat loss at just 1.44 wt%, 1.55 wt%, 1.33 wt% and 1.40 wt% chelate to gas product for Cu-MEA, Cu-DEA, Fe-EDTA, and NiMEA respectively. This represents the lowest possible limit. In addition to the potential health hazards which include cancer and memory loss, this is a significant value loss when compared to the recommended 37.73MJ/m3 for sales gas.